What’s in a Name? The Tricky Issue of Diagnosing Juvenile Temporal Arteritis When Histological Findings are not Consistent - Castellani, Chiara; d’Amati, Giulia; Cerbelli, Bruna; Biffoni, Marco; Perricone, Carlo; Alessandri, Cristiano; Conti, Fabrizio; Scrivo, Rossana (Archives of Clinical and Medical Case Reports, 2022)
Juvenile Temporal Arteritis (JTA) is a rare vasculitis characterized by a nodule occurring without previous trauma. We report the case of a young woman with a lesion clinically suggesting JTA, but histologically consistent with Angiolymphoid Hyperplasia with Eosinophilia (ALHE). A 25-year-old woman casually noticed a pulsatile, not erythematous, 2 x 0.5 cm lump in her right temporal area, without previous trauma. She denied visual impairment, difficulties in mastication, and headache. Erythrocyte sedimentation rate and C-reactive protein were normal and no peripheral eosinophilia was recorded. An ultrasound scan of the temporal artery showed the “halo sign”. The biopsy revealed proliferating vessels with plump eosinophilic endothelial cells surrounding the temporal artery, severe luminal stenosis, and lymphocyte and eosinophil infiltrate. Although the clinical features were consistent with JTA, a histological diagnosis of ALHE was established. ALHE usually presents with multiple, itchy, erythematous nodules or plaques of the scalp and the neck. Unlike ALHE, the overlying skin of the lesion in JTA is usually normal, while the “halo sign” may be present in both diseases. Furthermore, both JTA and ALHE show lymphocyte and eosinophil infiltrate and vascular proliferation. Although overlap conditions may occur, we observed a rare case with incongruous clinical and histological aspects, in which the clinical pattern of JTA matched the histological features of ALHE. JTA and ALHE might be considered as part of the spectrum of a single vascular disorder.